Efficacy and safety of dual antiplatelet therapy after percutaneous coronary drug-eluting stenting: A network meta-analysis. Issue 42 (21st October 2022) - Luo, Lin; Wang, Shenglin; Tang, Kai; Yang, Xu; Wu, Jianli; Wang, Dan; Xu, Liqiong; Feng, Tao; Li, Dejin; Ran, Jiuju; Li, Debo; Zhang, Li; et al.
Abstract : Background: To evaluate the efficacy and safety of dual antiplatelet regimens after coronary drug-eluting stenting by network meta-analysis (NMA). Methods: PubMed, The Cochrane Library, Embase, and Web of Science databases were electronically searched to collect randomized controlled trials (RCTs) of the comparison of different dual antiplatelet regimens after coronary drug-eluting stenting from inception to September 1st, 2021. Two reviewers independently screened literature, extracted data, and assessed the risk bias of included studies. Stata 16.0 software was used for NMA. Results: A total of 27 RCTs involving 79, 880 patients were included. The results of NMA: in terms of myocardial infarction (MI), other 3 interventions were higher than the long-term dual antiplatelet therapy (L-DAPT) (the standard dual antiplatelet therapy [Std-DAPT] [odds ratio [OR] = 1.82, 95%confidence interval [CI]: 1.49-2.21), the aspirin monotherapy after short-term dual antiplatelet therapy (S-DAPT + As) (OR = 2.06, 95%CI: 1.57-2.70), the P2Y12 inhibitor monotherapy after short-term dual antiplatelet therapy (S-DAPT + P2Y12) (OR = 1.71, 95%CI: 1.29-2.28)]. In terms of stent thrombosis, other 3 interventions were higher than L-DAPT [Std-DAPT (OR = 2.18, 95%CI: 1.45-3.28), S-DAPT + As (OR = 2.32, 95%CI: 1.52-3.54), S-DAPT + P2Y12 (OR = 2.31, 95%CI: 1.22-4.36)]. There was no statistically significant difference among the 4 interventions in prevention of stroke and all-cause mortality ( P  > .05). In terms of cardiovascular and cerebrovascular adverse events, other 3 interventions were higher than L-DAPT (Std-DAPT [OR = 1.28, 95%CI: 1.12-1.45], S-DAPT + As [OR = 1.27, 95%CI: 1.09-1.48], S-DAPT + P2Y12 [OR = 1.24, 95%CI: 1.01-1.52]). In terms of safety, bleeding rate of other 3 interventions were lower than L-DAPT (Std-DAPT [OR = 0.67, 95%CI: 0.52-0.85], S-DAPT + As [OR = 0.51, 95%CI: 0.39-0.66], S-DAPT + P2Y12 [OR = 0.36, 95%CI: 0.26-0.49]). Two interventions were lower than L-DAPT (S-DAPT + As [OR = 0.77, 95%CI: 0.65-0.90], S-DAPT + P2Y12 [OR = 0.54, 95%CI: 0.44-0.66]). S-DAPT + As was higher than L-DAPT (OR = 1.42, 95%CI: 1.10-1.83). Conclusions: S-DAPT + P2Y12 has the lowest bleeding risk, while L-DAPT has the highest bleeding risk. In the outcome of MI, stent thrombosis, and cardiovascular and cerebrovascular adverse events, L-DAPT has the best efficacy. In the outcome of stroke and all-cause mortality, the 4 interventions were equally effective.